2019
DOI: 10.1186/s40425-019-0507-2
|View full text |Cite
|
Sign up to set email alerts
|

Human double negative T cells target lung cancer via ligand-dependent mechanisms that can be enhanced by IL-15

Abstract: BackgroundThe advents of novel immunotherapies have revolutionized the treatment of cancer. Adoptive cellular therapies using chimeric antigen receptor T (CAR-T) cells have achieved remarkable clinical responses in B cell leukemia and lymphoma but the effect on solid tumors including lung cancer is limited. Here we present data on the therapeutic potential of allogeneic CD3+CD4−CD8− double negative T (DNT) cells as a new cellular therapy for the treatment of lung cancer and underlying mechanisms.MethodsDNTs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 44 publications
1
65
0
Order By: Relevance
“…In addition to cancer types presented in this study, Xu and colleagues showed that DNTs could target pancreatic carcinoma in a xenograft model (35), and we observed significantly inhibited non-small cell lung cancer progression after DNT treatment in xenograft models (manuscript submitted, ref. 36). Notably, DNTs from a single donor could kill cancer cells of different origins (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to cancer types presented in this study, Xu and colleagues showed that DNTs could target pancreatic carcinoma in a xenograft model (35), and we observed significantly inhibited non-small cell lung cancer progression after DNT treatment in xenograft models (manuscript submitted, ref. 36). Notably, DNTs from a single donor could kill cancer cells of different origins (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Lee J et al [36] showed that the inhibitory effects of DNTs on leukemia cell toxicity were largely induced by perforin/GZMB. Yao J et al [68] also showed that perforin/GZMB was involved in the process of killing NSCLCs by allogeneic DNTs.…”
Section: Granzyme/perforin-mediated Target Cell Apoptosismentioning
confidence: 98%
“…Chen B et al [67] demonstrated the feasibility and benefits of using DNTs after conventional chemotherapy. Yao J et al [68] recently reported that IL-15 enhanced the killing effect of DNTs. Fang et al [69] showed that DNT tumor infiltration increased when combined with anti-PD-1 treatment, which enhanced DNT cell-mediated antitumor effects.…”
Section: Recent Progress In Dnt-based Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations